2008
DOI: 10.1103/physrevlett.100.084502
|View full text |Cite
|
Sign up to set email alerts
|

Noncontinuous Froude Number Scaling for the Closure Depth of a Cylindrical Cavity

Abstract: A long, smooth cylinder is dragged through a water surface to create a cavity with an initially cylindrical shape. This surface void then collapses due to the hydrostatic pressure, leading to a rapid and axisymmetric pinch-off in a single point. Surprisingly, the depth at which this pinch-off takes place does not follow the expected Froude 1=3 power law. Instead, it displays two distinct scaling regimes separated by discrete jumps, both in experiment and in numerical simulations (employing a boundary integral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 17 publications
5
45
1
Order By: Relevance
“…Continuing the simulation, these nodes eventually form the tip of the top and bottom jets. These numerical simulations have shown excellent agreement with experiments for different impact geometries [4,20] and we verified carefully that our results are independent of numerical parameters such as node density and time stepping. The influence of air is neglected.…”
supporting
confidence: 69%
“…Continuing the simulation, these nodes eventually form the tip of the top and bottom jets. These numerical simulations have shown excellent agreement with experiments for different impact geometries [4,20] and we verified carefully that our results are independent of numerical parameters such as node density and time stepping. The influence of air is neglected.…”
supporting
confidence: 69%
“…The numerical details, including the "surface surgery" needed to accurately capture the transition from the cavity collapse process to the jet ejection, are given elsewhere [see Gekle et al (2009a); Bergmann et al (2009)]. These simulations have shown excellent agreement with experimental high-speed recordings and particle image velocimetry measurements [Bergmann et al (2006); Gekle et al (2008Gekle et al ( , 2009a; Bergmann et al (2009)]. The simulation stops when the downward jet hits the disc surface.…”
Section: Disc Impact Simulationssupporting
confidence: 50%
“…The differences pointed out above set our system somewhat apart from similar studies [Duclaux et al (2007); Glasheen & McMahon (1996)]. The experimental realization of the setup to which the numerical simulations presented are referred, is described by Bergmann et al (2006Bergmann et al ( , 2009Gekle et al (2008Gekle et al ( , 2009a, who show that boundary-integral simulations are in excellent agreement with experiments. In addition, potential flow numerical simulations to study of the type of Worthington jets ejected after bubble pinch-off from an underwater nozzle sticking into a quiescent pool of water [Manasseh et al (1998) This paper is organized as follows: In section 2 we present the three different numerical methods used.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10 shows a parametric plot of the solutions just before pinch-off (10a) and an experimental image at the same time (10b). We can improve on this result by using the same axisymmetric boundary integral code that was used in (Bergmann et al 2006;Gekle et al 2008Gekle et al , 2009a) to obtain the undisturbed cavity profile R(z, t) which has been found to be in very good agreement with the experimental results (Bergmann et al 2009b) and again use equation (3.11) to superimpose the effect of the disturbance in exactly the same manner as described above. This procedure gives the shape in figure (10c) which is very similar to the experimental picture, capturing even small details.…”
Section: The Structure Of the Cavitymentioning
confidence: 99%
“…The kinetic energy of the flow is focused into a vanishing small volume with a velocity whose magnitude diverges as the pinch-off moment is approached. Several experimental and theoretical scenarios have been recently considered in the study of this problem: a bubble rising from a capillary (Longuet-Higgins, Kerman & Lunde 1991;Oguz & Prosperetti 1993;Burton, Waldrep & Taborek 2005;Thoroddsen, Etoh & Takehara 2007), bubbles in a co-flowing liquid (Gordillo, Sevilla, Rodríguez-Rodríguez & Martínez-Bazán 2005;Bergmann, Andersen, van der Meer & Bohr 2009a), an initially necked bubble (Eggers, Fontelos, Leppinen & Snoeijer 2007), and cavities created through impact (Bergmann, van der Meer, Stijnman, Sandtke, Prosperetti & Lohse 2006;Gekle, van der Bos, Bergmann, van der Meer & Lohse 2008;Bergmann, van der Meer, Gekle, van der Bos & Lohse 2009b). Depending on the case, the collapse might be initiated by surface tension, external flow, or hydrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%